Tracing the Origins and Development of Madrasah Education in Sri Lanka - Mohamed Rislan; Zuraidah Binthi Abdullah; Mohammad Ismath Ramzy (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2025)
The Madrasah education system in Sri Lanka, established in the late 19th Century, has long been an important aspect of the country’s educational landscape. This study explores the establishment, development, and contextual relevance of Madrasah education in Sri Lanka, focusing on its ability to address contemporary challenges. An integrative literature review, grounded in Phillips and Ochs’ theory of education policy borrowing, was employed to examine the historical and current state of Madrasah education. The findings reveal that Madrasah education in Sri Lanka has evolved through three distinct phases: the Monolithic Madrasah before colonization (pre-1505 CE), Indigenous religious Madrasah during colonization (1505 CE to the late 19th Century), and the Indian Model Madrasah that persists today. Despite its historical significance, contemporary Madrasah education has failed to adapt to the country’s socio-political and educational developments. These findings highlight the need for a comprehensive reform to ensure the relevance of Madrasah education, offering valuable insights for policymakers and educators to enhance the integration of Madrasahs into Sri Lanka’s broader educational system.